2002
DOI: 10.1002/hipo.1113
|View full text |Cite
|
Sign up to set email alerts
|

Age‐related differences in the medial temporal lobe responses to emotional faces as revealed by fMRI

Abstract: Age-related differences involved in the neural substrates of emotional face perception were investigated in young and old healthy volunteers. The subjects were scanned using functional magnetic resonance imaging while they were judging the gender of faces with negative, positive, or neutral emotional valence. The results showed that both the predominant activation in young subjects and reduced activity in old subjects contributed to a significant age difference in the left amygdala during the perception of neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
126
2
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(154 citation statements)
references
References 49 publications
25
126
2
1
Order By: Relevance
“…(2007) have shown that brain reactivity to negative emotional input decreased linearly with age, while it remained stable for positive input. Finally, an age-related reduced reactivity of the amygdala has been described for negative facial expressions and pictures, but not for positive ones (e.g., Gunning-Dixon et al, 2003;Iidaka et al, 2002;Mather et al, 2004). It is therefore possible that the age-related changes in motivation towards positive input and the bias to positivity, which appear to be linked with changes in brain function, underlie the pattern of results reported here.…”
Section: Explanatory Hypothesesmentioning
confidence: 45%
See 1 more Smart Citation
“…(2007) have shown that brain reactivity to negative emotional input decreased linearly with age, while it remained stable for positive input. Finally, an age-related reduced reactivity of the amygdala has been described for negative facial expressions and pictures, but not for positive ones (e.g., Gunning-Dixon et al, 2003;Iidaka et al, 2002;Mather et al, 2004). It is therefore possible that the age-related changes in motivation towards positive input and the bias to positivity, which appear to be linked with changes in brain function, underlie the pattern of results reported here.…”
Section: Explanatory Hypothesesmentioning
confidence: 45%
“…Converging evidence supports the link between this motivational shift and age-related changes in how we recognize and process emotional stimuli (GunningDixon et al, 2003;Iidaka et al, 2002;Jacques, Dolcos, & Cabeza, 2008;Kisley, Wood, & Burrows, 2007;Mather et al, 2004;Williams et al, 2006). For instance, Williams and colleagues (2006) analyzed the recognition of fearful, happy and neutral facial expressions from 12 to 79 years of age using behavioral, neurophysiological and neuroimaging methods.…”
Section: Emotion Recognition In Music Changes Across the Adult Life Spanmentioning
confidence: 98%
“…While amygdala and fusiform gyrus activity decreases, prefrontal activity increases in healthy older men and women (460 years) in comparison to young adults (o30 years) (Iidaka et al, 2002;Gunning-Dixon et al, 2003;Mather et al, 2004;Tessitore et al, 2005). However, to our knowledge, amygdala reactivity during midlife has not been investigated previously.…”
Section: Discussionmentioning
confidence: 86%
“…Amygdala activity has been found in several ToM neuroimaging studies that emphasized socio-emotional facets of ToM such as reading social and emotional cues from others ( Baron-Cohen, et al, 1999b;Gallagher & Frith, 2004;Vollm et al, 2006). In addition, the amygdala is known to be active when subjects are exposed to emotional faces (Baron-Cohen et al, 1999b;Iidaka et al, 2002;Morris, deBonis, & Dolan, 2002;Morris et al, 1996). Thus, the greater activity in this area for the adult group may indicate that adults were more aware of emotional cues in the faces in the cartoon ToM task than children.…”
Section: Discussionmentioning
confidence: 99%